2020
DOI: 10.1210/clinem/dgaa249
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Hypothalamo-Pituitary Axis in Association With Reduced SHH Underlies the Pathogenesis of NOTCH-Deficiency

Abstract: Context In human, Sonic hedgehog (SHH) haploinsufficiency is the predominant cause of holoprosencephaly, a structural malformation of the forebrain midline characterized by phenotypic heterogeneity and incomplete penetrance. The NOTCH signaling pathway has recently been associated with holoprosencephaly in humans, but the precise mechanism involving NOTCH signaling during early brain development remains unknown. Objective The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…However, a large-scale study would be needed to confirm our findings. One possibility consistent with these observations is that congenital hypopituitarism often has a digenic or oligogenic inheritance, as has been suggested (Hamdi-Rozé et al, 2020), although data for this hypothesis has been reported only in a small number of families to date (Zwaveling-Soonawala et al, 2018). In our study, 2 out of 13 families showed a possible oligogenic etiology.…”
Section: Discussionsupporting
confidence: 89%
“…However, a large-scale study would be needed to confirm our findings. One possibility consistent with these observations is that congenital hypopituitarism often has a digenic or oligogenic inheritance, as has been suggested (Hamdi-Rozé et al, 2020), although data for this hypothesis has been reported only in a small number of families to date (Zwaveling-Soonawala et al, 2018). In our study, 2 out of 13 families showed a possible oligogenic etiology.…”
Section: Discussionsupporting
confidence: 89%
“…By contrast, HES5 expression is dramatically reduced in BMP-exposed embryos (Figure 6Q, S-S”, U’). Notch maintains the progenitor state in chicken hypothalamus (Hamdi-Rozé et al, 2020, Place et al, 2022, Ratié et al, 2013, Ratié et al, 2014, Ware et al, 2016) so the loss of HES5 in BMP-treated embryos may be associated with ectopic neurogenesis. Despite this result, no clear differences in DLL1 and ELAVL4 expression were seen in the residual hypothalamic domain in BMP-treated embryos (Figure 6Q, U’).…”
Section: Resultsmentioning
confidence: 99%
“…BMPs and low WNT levels direct the specification of posterior tuberal progenitors, through upregulation of TBX2/FGF10; TBX2/TBX3 in turn downregulate SHH (Manning et al, 2006; Trowe et al, 2013). SHH and Notch signalling, by contrast, direct anterior tuberal progenitor growth and neurogenesis (Blaess et al, 2014, Carreno et al, 2017, Corman et al, 2018, Dupé et al, 2011, Fu et al, 2017, Ratié et al, 2013, Shimogori et al, 2010, Aujla et al, 2013, Hamdi-Rozé et al, 2020, Orquera et al, 2016, Ratié et al, 2014, Szabó et al, 2009, Ware et al, 2016). Studies in mouse furthermore suggest that a delicate balance of SHH and BMP signalling directs tuberal hypothalamic development (Corman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Haploinsufficiency for NOTCH pathway components in some patients with HPE further suggests that NOTCH-dependent facilitation of SHH signaling is required for forebrain formation (Dupe et al, 2011). This conclusion is supported by loss of NOTCH-dependent SHH activity in the embryonic mouse and chick forebrains following pharmacological or genetic perturbation of NOTCH activity, defects that include disruption of the hypothalamopituitary axis (Hamdi-Roze et al, 2020).…”
Section: Discussionmentioning
confidence: 96%